Study of Trans-1,2-Dichlorocyclohexane Absorbed in Zeolites - Zhang, Hui; Kyung Kim, Chan (Asian Journal of Chemistry, 2012)
The behaviour of trans-1,2-dichlorocyclohexane (T12D) adsorbed inside zeolite NaY has been investigated by molecular dynamics (MD) simulations. The ratio of Si/Al is 2.35 in the NaY zeolite. The NaY zeolite is modeled using the average-T model with rigid frame. The results have clearly shown that the adsorption of trans-1,2-dichlorocyclohexane strongly depended on the zeolite framework structure and the presence of charge-balancing cations. Combined results show that ee conformer is favorable when trans-1,2-dichlorocyclohexane molecule is adsorbed in faujasite type zeolite.